RELEVANSI PRINSIP NON DISKRIMINASI DALAM WTO DARI SUDUT PELAYANAN JASA PARIWISATA BALI - Setiawan, I Kadek (Jurnal Advokasi, 2017)
A targeted and appropriate tourism development program in order to increase the number of foreign tourist arrivals is needed. Businessmen engaged in the tourism business must be able to provide non-discriminatory services to tourists, which means services that do not distinguish between domestic and foreign tourists. It must be obeyed because Indonesia is a member of WTO, besides the existence of regulations regulating discriminative acts in tourism such as Tourism Act and City Regulation, Article 8 number 1 of Code of Ethics of World Tourism and in Article 26 Letter C point of view of National Law Principle of non-discrimination. In practice found the existence of violations of the provision of tourism services that indicate the existence of elements of discrimination through the internet media. The violation of tourism in discriminative elements is contradictory to Bali Province Regional Regulation Year 2012 on Balinese Cultural Tourism, and sanction which can be given is administrative sanction.